Effects of exercise during pregnancy in women with short cervix: Secondary analysis from the Italian Pessary Trial in singletons. (October 2018) - Saccone, Gabriele; Berghella, Vincenzo; Venturella, Roberta; D'Alessandro, Pietro; Arduino, Bruno; Raffone, Antonio; Giudicepietro, Antonia; Visentin, Silvia; Vitagliano, Amerigo; Martinelli, Pasquale; Zullo, Fulvio; ,
Abstract: Objective: To evaluate effects of exercise during pregnancy in asymptomatic singleton pregnancies without prior spontaneous preterm birth (SPTB) but with short transvaginal ultrasound cervical length (TVU CL). Study design: This is a secondary analysis of the Italian Pessary Trial for the Italian Preterm Birth Prevention (IPP) Working Group . In the original prospective randomized controlled trial asymptomatic singleton pregnancies without prior SPTB but with TVU CL ≤ 25 mm at 18 0/6–23 6/7 weeks were randomized into 1:1 ratio to either cervical pessary or no pessary. During their follow-up visits, women were asked about their activity. For the purpose of this secondary analysis, women were classified in the following groups, using the information obtained in the follow-up visit one month after randomization: 1) Exercise group, defined as women performing exercise ≥2 days a week for ≥20 min each day. 2) No exercise group, defined as women performing exercise <2 days a week for ≥20 min each day. The primary outcome of this secondary analysis was PTB < 37 weeks. Results: 300 women were included in this analysis. 99 (33.0%) were included in the exercise group. 201 (67.0%) were included in the no exercise group. Of the 201 women in the no exercise group, 90 (44.8%) affirmed that they had reduced their activity after the diagnosis of short cervix despite the research staff recommendations, while the other 111 (55.2%) women performed a sedentary life style even before the diagnosis of short cervix. PTB < 37 weeks occurred in 22 women (22.2%) in the exercise group, and 66 women (32.8%) in the no exercise group (aOR 0.65, 95% CI 0.33–1.03). Conclusion: In asymptomatic singleton pregnancies with short cervix, performing exercise ≥2 days a week for ≥20 min each day does not increase the risk of PTB but is indeed associated with a non-significant reduction in PTB < 37 weeks by 32%.